PTU-211 Novel techniques in the treatment of cryptoglandular fistula in ano: a systematic review. (22nd June 2015) - Narang, SK; Keogh, K; Alam, N; Pathak, S; Daniels, I; Smart, N
Abstract : Introduction: Fistula in ano represents a complex disease process that can be particularly challenging to treat. Several newer techniques have been developed with the intention of achieving high success rates and minimising damage to the anal sphincter complex. The aim of this systematic review was to review the published literature for novel treatment strategies and assess its effectiveness. Method: A systematic review of all English language literature relevant to novel treatment strategies for cryptoglandular fistula in ano, published between 1 January 2007 and 31 Dec 2014 was carried out using MEDLINE, EMBASE and the Cochrane Library of Systematic Reviews/Controlled Trials for relevant literature. Relevant articles were identified, quality assessed using the MINORS criteria and the data were extracted by two researchers independently. The identified novel techniques were assessed with regards to the surgical procedure, fistula healing rate, length of follow up and complication rates. Results: A total of 70 potential articles were identified from the literature search. Using the predefined inclusion and exclusion criteria, 21 articles were included for the final analysis, data extraction and data synthesis. Apart from two RCT, all were retrospective or prospective case series. The identified studies reported the use of novel biomaterials (adipose derived stem cells, platelet rich plasma, Human acellular dermal matrix (ADM), Permacol™ solid implant/suspension, Acellular Dermal Matrix (ADM), Acellular Extracellular Matrix (AEM), Energy devices (Fistula laser closure-FiLaC), new types of seton sutures (Comfort Drain and self-locking cable tie), Hybrid techniques (BioLIFT, LIFT-Plug and Permacol injection-advancement flap), OTSC TM Proctology clip system and Video assisted anal fistula treatment (VAAFT). The success rates of the various techniques ranged from 37.3% to 100% over a follow up period ranging from 4–81 months without any major disturbance to continence. Conclusion: This systematic review has demonstrated that there have been some pioneering technological advances to treat complex cryptoglandular fistula in ano however most of these are in an early stage of evolution. Due to the significant variation in the methodology, study design, outcome reporting of the included studies, it is not possible to meaningfully compare and contrast the described novel techniques. As with most new procedures, the early promising and enthusiastic results are often difficult to reproduce. Longer follow up data is not currently available. Disclosure of interest: None Declared.